2020
DOI: 10.4149/bll_2020_064
|View full text |Cite
|
Sign up to set email alerts
|

Can repetitive transcranial magnetic stimulation of the visual cortex ameliorate the state of patients with visual snow?

Abstract: AIMS: Visual snow is a neurological condition, for which an effective treatment has not been established. The aim of this study was to fi nd whether Repetitive Transcranial Magnetic Stimulation (rTMS) can improve the state of patients suffering from visual snow. To our knowledge, no other group has tested this method in the treatment of visual snow. METHODS: We applied rTMS of 10 and 10+1 Hz on the visual cortices of 9 patients with visual snow. Sham stimulation with the vertex as the target site was also test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
8
0
2
Order By: Relevance
“…Grey et al applied TMS at 10 and 10 + 1 Hz over occipital brain areas during 20 sessions in nine patients. They found an improvement of VS intensities after the 10 + 1 Hz application, but no significant difference of the comparison to Sham or 10 Hz ( 64 ).…”
Section: Resultsmentioning
confidence: 95%
“…Grey et al applied TMS at 10 and 10 + 1 Hz over occipital brain areas during 20 sessions in nine patients. They found an improvement of VS intensities after the 10 + 1 Hz application, but no significant difference of the comparison to Sham or 10 Hz ( 64 ).…”
Section: Resultsmentioning
confidence: 95%
“…Patients also report wearing sunglasses to reduce light sensitivity, improvement with healthy sleep and diet habits, and learning how to ignore symptoms [50]. Repetitive transcranial magnetic stimulation (rTMS) as a potential treatment for VSS is in the pipeline; a preliminary study in nine patients showed a potential improvement [80] and an open-label treatment trial is ongoing [81]. A clinical trial using neurofeedback is also currently ongoing, with the idea of teaching patients to downregulate activity in different regions of the visual cortex (NeurofeebackSnow, NCT04902365).…”
Section: Treatmentmentioning
confidence: 99%
“…18 In some neurodegenerative and ocular diseases, VS was refractory to any treatment. 18 Color filters of the yellowblue color spectrum 41 and repetitive transcranial magnetic stimulation of the visual cortex 42 are also helpful in some patients with VSS. These strategies can be used to treat secondary VS in refractory cases.…”
Section: Discussionmentioning
confidence: 99%